2013
DOI: 10.1093/intimm/dxt040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modifications on siRNAs avoid Toll-like-receptor-mediated activation of the hepatic immune system in vivo and in vitro

Abstract: Our data indicate that siRNAs activate endosomal Toll-like receptors in different liver-derived cell types to various degrees, in vitro. LNP-formulated siRNA selectively leads to hepatic knock-down of target genes in vivo. Here, off-target immune responses are restricted to non-parenchymal liver cells. However, 2'-O-methyl modifications of siRNA largely avoid immune-stimulatory effects, which is a crucial prerequisite for the development of safe and efficient RNA-interference-based therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Here, LNP-formulated siRNAs led to significant up-regulation of Ifn-b in NPC (p = 0.0003). This kind of initial and transient off-target effect had been shown to be a sequence-dependent, TLR-mediated, immune response (Broering et al, 2013). The Isg15 knockdown in PMH could be verified by western blot analysis.…”
Section: Lnp-formulated Isg15-specific Sirnas Lead To Hepatocyte Specmentioning
confidence: 75%
“…Here, LNP-formulated siRNAs led to significant up-regulation of Ifn-b in NPC (p = 0.0003). This kind of initial and transient off-target effect had been shown to be a sequence-dependent, TLR-mediated, immune response (Broering et al, 2013). The Isg15 knockdown in PMH could be verified by western blot analysis.…”
Section: Lnp-formulated Isg15-specific Sirnas Lead To Hepatocyte Specmentioning
confidence: 75%
“…Although inflammatory responses were observed early in vivo experiments with degenerate NAPs (i.e. REP 2006), consistent with activation of the innate response212 the antiviral activities of NAPs containing sequences and naturally occurring nucleotide modifications designed to block recognition by pattern receptors13141516171819, persist and are not accompanied by pro-inflammatory effects in vivo or in human patients351220. However since many of the antiviral effects of NAP therapy in HBV infection are similar to those observed with immunotherapy, a more rigorous examination of immunostimulatory effects of NAPs optimized for therapeutic use was conducted in primary cultures of human parenchymal and non-parenchymal liver cells and peripheral blood mononuclear cells.…”
mentioning
confidence: 85%
“…In this section, major challenges, namely, 1) instability in the blood circulation, 2) targeting to specific cells of interest, and 3) activation in response to the tumor microenvironment (TME), 174 for systemic AuNP delivery in terms of cancer diagnosis and phototherapeutics are discussed (Figure 2). …”
Section: Barriers To the Translation Of Aunps For Cancer Theranosticsmentioning
confidence: 99%
“…76,178,179 In addition to these stabilizing components, long-circulating NPs have also been developed where the NP surface is coated with the cellular membrane of red blood cells (RBCs) and leukocytes. 150,154,174,175 As an alternative stealth coating material, the membrane of these cells completely covers the NP surface with their "selfmarkers" (ie, proteins, glycans, and acidic sialyl moieties), and the resultant NPs, recognized as the host's own cells, can actively evade the immune system. For example, Piao et al 160 reported that the RBC-coated gold nanocages exhibited longer blood retention compared with the PEGylated counterparts.…”
mentioning
confidence: 99%